1980
DOI: 10.1029/gl007i004p00259
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term 1.5 GHz amplitude scintillation measurements at the magnetic equator

Abstract: The diurnal and seasonal behavior of long‐term (approximately 20 months) 1.54 GHz amplitude scintillation measurements under low sunspot conditions observed at Huancayo, Peru are presented. The measurements refer to a low elevation geometry in the E‐W plane at the magnetic equator. The data show clear equinoctial maxima of occurrence and confinement to the pre‐midnight hours. There is a total absence of scintillations during the May‐July period. The present results are critically compared to previously reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 11 publications
4
12
0
Order By: Relevance
“…These aspects suggest that the Ionospheric-Atmospheric conditions over SLZ (CXI) are most (least) favourable for the generation of ESF, among three stations. ROJ has % occurrence characteristics more similar towards SLZ except that the season of maximum occurrence of ESF with plume is during equinox, which is a known feature from earlier studies (Basu et al, 1980;Sobral et al, 2002;de Paula et al, 2011). However, it is interesting to note that the season of maximum occurrence of all ESF events (i.e.…”
Section: Seasonal and Longitudinal Occurrences Of Spread F Parametersmentioning
confidence: 53%
“…These aspects suggest that the Ionospheric-Atmospheric conditions over SLZ (CXI) are most (least) favourable for the generation of ESF, among three stations. ROJ has % occurrence characteristics more similar towards SLZ except that the season of maximum occurrence of ESF with plume is during equinox, which is a known feature from earlier studies (Basu et al, 1980;Sobral et al, 2002;de Paula et al, 2011). However, it is interesting to note that the season of maximum occurrence of all ESF events (i.e.…”
Section: Seasonal and Longitudinal Occurrences Of Spread F Parametersmentioning
confidence: 53%
“…While the first two points above are expected from the known climatology of scintillation at L-band frequencies (Aarons and Basu, 1994;Basu et al, 1980), the third point, at first impression, seems to indicate that the peak activity is biased equator-ward from the anomaly crests by 2 • -3 • in magnetic latitude. However, this is not the case as the anomaly crests move equator-ward after the passage of the sunset terminator as displayed in Fig.…”
Section: Latitudinal Position Of Irregularity Activitymentioning
confidence: 97%
“…Previous studies found that ionospheric structures, such as the sporadic E (Es), equatorial plasma irregularities (EPIs), equatorial ionization anomaly (EIA), polar patches, and auroral blobs, can cause additional influence on the GNSS signal (e.g., Basu et al, 1980Basu et al, , 2002Crowley et al, 2000;Kintner et al, 2004Kintner et al, , 2007Yue et al, 2016). These ionospheric structures with spatial scales from hundreds of kilometers down to meters produce rapid fluctuations of the received signal phase and amplitude termed as scintillations.…”
Section: Introductionmentioning
confidence: 99%
“…Ionospheric scintillations from ground-based measurements have been widely used to investigate the morphology of the ionosphere (e.g., Basu et al, 1980;Aarons, 1982;Spogli et al, 2009;Jin et al, 2014;Clausen et al, 2016). Some low Earth orbit (LEO) missions, such as the CHAllenging Minisatellite Payload (CHAMP) and the Constellation Observing System for Meteorology, Ionosphere, and Climate (COSMIC), were equipped with GPS radio occultation (RO) instruments with high temporal resolution, which have also been applied for investigating the morphology of Published by Copernicus Publications on behalf of the European Geosciences Union.…”
Section: Introductionmentioning
confidence: 99%